(untitled) (Biological Sciences - PJSIR, 2001)
As an approach to resolve the haptenised proteins involved in the production of dermatoses 2, 4-dinitrochlorobenzene and 2, 4-dinitrofluorobenzene were chosen as model haptens with a well established and understood mechanism of protein preactivity. These haptens were applied to mouse skin in Vivo. Prior to sacrifice after 6 days, control and treated skin was homogenized and the microsomal proteins examined by dialysis, gel permeation and SDS-PAGE. Rather unexpectedly only one protein band in DNFB treated skin, appeared to have become labelled with an apparent molecul ar mass of 47,000 Da.